The Response of the Philippine Government in Handling the COVID-19 Pandemic - Saphire, Anisya Olivia; Nurkhasanah, Dini Septianti; Resdifianti, Femri (Journal of ASEAN Dynamics and Beyond, 2020)
All countries in Southeast Asia have faced the threat of widespread outbreaks of Coronavirus (COVID-19). One of the countries in Southeast Asia that experienced the most significant impact from COVID-19 is the Philippines. This paper discusses the COVID-19 threat as a form of non-traditional human security threat and the Philippines Government's need to carry out securitization and response measures to prevent the spread of the threat. In addition, this paper also explains the impact of COVID-19 in the Philippines and the new normal conditions after the lockdown was put in place by the government. This descriptive analysis shows that the COVID-19 outbreak, as a non-traditional security threat, impacted various Philippines' sectors. This result also indicates the Philippine government's response in dealing with the impact arising from the COVID-19 outbreak and the implementation of new normal to drive the economy. Therefore, we divide the discussion into four parts: First, an overview describes the Philippines' COVID-19 cases. Second, explain the impact of a pandemic in various fields. Third, define the response of the Philippine Government in dealing with COVID-19. Fourth, describing the challenges in dealing with COVID-19 in the Philippines and the new normal situation in force in the Philippines.